Anlotinib Combined With Chemotherapy for Recurrence of Pulmonary Sarcomatoid Cancer Previously Surgically Treated: A Case Report and Literature Review - Li, Jing; Liang, Hejun; He, Jian; Sui, Xin; Qin, Yanru (Frontiers in Oncology, 2021)
Background: Pulmonary sarcomatoid cancer (PSC) is a very rare subtype of poorly differentiated non-small-lung-cancer (NSCLC) with very poor prognosis. To date, the optimal treatment for PSC has not been elucidated, and the efficacy of anlotinib in PSC has not been previously reported. Case Presentation: A 77-year-old male patient was admitted with cough, expectoration, and blood-stained sputum for one month. CT showed a soft mass in the inferior lobe of the right lung, which was diagnosed as spindle cell carcinoma (PSC) by histopathology. A videothoracoscopic right lower lobectomy and mediastinal lymph node dissection procedure was performed on the patient, but the disease recurred one month after surgery. The patient was then given first-line chemotherapy with gemcitabine and albumin paclitaxel for one cycle, but the disease continued to progress. The patient then received anlotinib combined with second-line chemotherapy (dacarbazine and cis-platinum) for six cycles, and the response reached complete remission (CR). Then the patient was given maintenance therapy with anlotinib alone, and the disease was still stable at the most recent reexamination. Progression-free survival (PFS) has lasted for more than two years, without any intolerable toxicity. Conclusion: This postoperative recurrent PSC patient achieved significant clinical benefits with anlotinib treatment. Our findings provide direct evidence of the efficacy of anlotinib in PSC. More studies are needed to confirm our observation.